Defamiliarization: A Formalism Study on How Words Can Create Compelling Narrative in Edgar Allan Poe’s The Tell-Tale Heart - Zamtrio Purbo; Nur Hidayat; Sri Wahyuni (International Journal of Research in Education, 2022)
Literary works are frequently used to express human expression through words, making literary works one of the unique mediums to express these expressions. The uniqueness lies within the language used to construct the story itself. Therefore, this study aims to uncover the factors that make a literary work great through formalism and defamiliarization theory, furthermore uncovering the impact of the factors on the story. Using a qualitative research method specifically close reading, this study describes how the strength of a short story The Tell-Tale Heart written by Edgar Allan Poe according to both formalism and defamiliarization theory can contribute to the construction of the story. The construction of the story relies on its tension which is delivered through the use of its imageries, form/structure, parallelism, etc. It can be concluded that the possession of the formalism elements helps the story to shape its nuance and its atmospheric storytelling